Pengaruh Variasi Penambahan Ragi dan Lamanya Waktu Fermentasi terhadap Hasil Fermentasi Etanol dari Serbuk Gergajian Kayu Ulin (Eusideroxylon zwageri T et B) - Ahmad Jauhari; Noor Mirad Sari (Jurnal Ilmu Kehutanan, 2007)
Effect of  Variation yeast addition and Duration of Fermentation on the Amount of Ethanol Produced from Sawdust of Ulin Wood (Eusideroxylon zwageri T et B)The research was aimed to assess the influence of different levels of yeast addition and duration of fermentation on the amount and percentage of ethanol produced from sawdust of ulin wood as raw material.Method used in this experiment was chemical hydrolysis of cellulose by using nitric acid (HNO3) as chemical agent. This substrate was inoculated into yeast cell (khamir) to convert glucose into ethanol. The amount of ethanol (ml) was obtained from distilled water (ml) multiplied by the azeotropic value of ethanol (95,5%), while the value  ethanol (%) obtained was from the amount of ethanol (ml) divided by the amount of distilled water (ml) multiplied by 100 percent.The study used a factorial design of 3 x 3 with 3 replications and the parameters used were A factor (amount of yeast) consisting of 5, 10, and 15 grams, respectively, and B factor (duration of fermentation) consisting of 1, 3, and 5 days, respectively. Significant differences of ANOVA at test levels of 5% and 1% will be continued by interaction test between the two factors to assess the influence of each factor on the amount and percentage of ethanol.Results indicated that the amount of yeast applied, duration of fermentation and interaction between the two gave very significant effects on the amount of ethanol (ml) and its percentage (%). Following the treatment on ulin wood sawdust, the lowest yield of ethanol was found at A1B1 treatment (5 g, 1 day) with. 1.69 ml, while the highest at A3B3 treatment (15 g, 5 day) with 5.19 ml. In terms of ethanol percentage, the lowest was found at A1B1 treatment with 9.4% and the highest at A3B2 treatment with 29.9%.